Amphiphilic γ-PGA nanoparticles administered on rat middle ear mucosa produce adjuvant-like immunostimulation in vivo. (October 2014) - Nilsson, Johan S.; Broos, Sissela; Akagi, Takami; Akashi, Mitsuru; Hermansson, Ann; Cayé-Thomasen, Per; Lindstedt, Malin; Greiff, Lennart
Abstract Conclusion: Amphiphilic biodegradable nanoparticles (NPs) composed of poly(γ-glutamic acid) conjugated with L-phenylalanine ethylester (γ-PGA-Phe NPs) applied on the rat middle ear mucosa produce an inflammatory type 1 response. The observation is of relevance for the use of γ-PGA-Phe NPs as a concomitant antigen delivery system and adjuvant measure in the context of vaccinations. Objectives: To examine effects of topical mucosal administration of γ-PGA-Phe NPs as a potentially combined antigen delivery system and adjuvant. Methods: γ-PGA-Phe NPs were administered on rat middle ear mucosa in a sham-controlled design and the response was monitored, focusing on soluble markers in mucosal surface liquids and on overall histopathology. Results: γ-PGA-Phe NPs produced a dose- and time-dependent inflammatory response characterized by generation of proinflammatory cytokines (IL-1α, IL-1β, IL-6, MIP-1α, and TNF-α) and associated histopathological changes.